Effect of extreme crop year on soil moisture in maize - Dóka, Lajos Fülöp (Acta Agraria Debreceniensis, 2010)
We examined the change of the time of water balance of soil in 25 years old experiment, on chernozem soil, in different croprotation systems (mono-, bi- and triculture) in two extreme cropyear in 2007 and 2009 in maizestock. According to our findings the values of waterdeficit of soil of maizestock were about 100 mm before the sowing time that grew because of considerable deficit of precipitation and high average temperature in months of summer. Values of waterdeficit achieved at the end of August the maximum and lessed a little bit to end of crop time. Decrease of waterstock stopped because of irrigation treatments in irrigated plots but the difference between two irrigation treatments (Ö1-Ö3) vanishedat the end of summer, waterdeficit were higher with 17 mm in monoculture in irrigated plot than value of not-irrigated plot. Considerabler precipitation in Jun effected on waterbalance of soils of three of crop-rotation systems favourable, rapid waterloss starting to april began to lessenat the end of May and started to increase from early in July. Precipitation in Jun had positiv effect on yield also.